School environment and individual factors influence oral health related quality of life in Brazilian children - Renan Vaz MACHRY; Jessica Klöckner KNORST; Fernanda TOMAZONI; Thiago Machado ARDENGHI (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to verify the influence of school environment and individual factors on oral health related quality of life (OHRQoL) in a representative sample of Brazilian schoolchildren. A cross-sectional study was conducted with 1,134 12-year-old schoolchildren from Santa Maria, Southern Brazil. Clinical variables were obtained from examinations carried out by calibrated individuals. In addition, parents/guardians answered a semi-structured questionnaire about sociodemographic characteristics. Contextual variables were obtained from the city's official database, including the mean income of the neighborhood in which the school was located and the Basic School's Development Index (IDEB) of the school. The Brazilian version of the Child Perception Questionnaire (CPQ11-14) was used to access OHRQoL. Data analysis was conducted using multilevel Poisson regression. Children studying in schools with a higher classification on the IDEB presented a lower CPQ11-14 mean score (rate ratio 0.80, 95%CI 0.74-0.88) than those studying in schools with a lower IDEB. Regarding individual variables, children with carious cavities, malocclusion, and gingival bleeding presented higher CPQ11-14 mean values than their counterparts. The same was observed in children from families with low socioeconomic status. School environment, and individual clinical and socioeconomic factors were associated with schoolchildren's OHRQoL.